Pengaruh Budaya Organisasi, Komitmen Organisasi Dan Stres Kerja Terhadap Turnover Intention Karyawan PT. Brahma Bina Bakti Mill Jambi - Maizul Rahmizal; Novia Lasmi (JURNAL PUNDI, 2021)
Fast traslate Icon translate     Fast traslate Icon translate Turnover intention is the intention of leaving an employee from a company and looking for alternatives to other companies or other jobs. Turnover intention is generated on the basis of the workload experienced by employees. This study aims to determine the relationship between organizational culture, organizational commitment and work stress and turnover intention on employees. The population of this study were employees who worked in the PT. Brahma Bina Bakti Mill Jambi as 162 people. The sample in this study was 62 people with sampling technique used was slovin formula. Therefore, the analysis of the data used is the statistical analysis in the form of multiple linear regression tests. These results indicate that partially, the variable organizational culture and organizational commitment has negative effect on the variable turnover intention. While, Variable work stress has positive effect on the variable turnover intention.